A Note on Physical and Mechanical Properties of Lagerstroemia speciosa (Jarul) from Kerala - Jain, J. D.; Dangwal, M. N. (Indian Forester, 1984)
Physical and mechanical properties of Lagerstroemia speciosa (Jarul), received from Karulal Range, Nilambur. Kerala and tested in green condition, have been reported and discussed. The results obtained have been compared with standard teak. It is found that values are lower than standard teak in general. Expected values based on strength specific gravity formulae have also been reported for comparison.